2015
DOI: 10.20955/r.2015.303-322
|View full text |Cite
|
Sign up to set email alerts
|

How Effective Is Central Bank Forward Guidance?

Abstract: In this paper, we use survey forecasts to investigate the impact of forward guidance on the predictability of future short-and long-term interest rates in four countries: New Zealand, Norway, Sweden, and the United States. New Zealand began providing forward guidance in 1997, Norway in 2005, and Sweden in 2007. The United States had two periods of implicit forward guidance: 2003-2005 and 2008-2011. Overall, we find little or no convincing evidence that forward guidance actually improves markets' ability to fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…In theory, such commitments are less powerful than introducing, for example, a nominal level target at the ELB. Our study therefore differs from Kool and Thornton (2015) who measure the effectiveness of forward guidance in terms of improved market participants' ability to forecast short-term interest rates and Svensson (2015) who empirically examined the predictability and credibility of policy rate forecasts. the New Keynesian model is at odds with the data because positive technology shocks are still expansionary when the ELB is binding.…”
Section: Introductionmentioning
confidence: 94%
“…In theory, such commitments are less powerful than introducing, for example, a nominal level target at the ELB. Our study therefore differs from Kool and Thornton (2015) who measure the effectiveness of forward guidance in terms of improved market participants' ability to forecast short-term interest rates and Svensson (2015) who empirically examined the predictability and credibility of policy rate forecasts. the New Keynesian model is at odds with the data because positive technology shocks are still expansionary when the ELB is binding.…”
Section: Introductionmentioning
confidence: 94%
“…Goodfriend (1993) suggested that the Fed attempts to counteract the effect of inflation shocks on long-term yields with preemptive increases in the funds rate. If his hypothesis is correct, long-term rates would increase with the funds rate only if market participants were not confident in the Fed's commitment to keep the EH is consistent with evidence is that neither market participants nor central bankers can predict the future path of short-term rates beyond a few months (e.g., Rudebusch, 2007, Goodhart and Lim, 2011, Andersson and Hofmann, 2010, Kool and Thornton, 2015. inflation low; if the market participants believed that the Fed would keep inflation in check, long-term rates would not respond to increases in the funds rate: Longterm yields and the funds rate would be uncorrelated when there were "inflation scares.…”
Section: The Funds Rate Targeting Hypothesismentioning
confidence: 68%
“…The market came to interpret (correctly) that the language indicated that the funds rate target would be increased 25 basis points the next meeting (e.g., Poole 2005). However, using survey data Kool and Thornton (2015) found that the FOMC's forward guidance policy had no effect on the predictability of short-term or long-term rates.…”
Section: The Policy Predictability Hypothesismentioning
confidence: 99%
“…Not all scholars are convinced about the effectiveness of FG beyond the near-term (e.g. Kool and Thornton, 2012;Filardo and Hofmann, 2014). Moessner et al (2017) suggest that central banks do not make commitments of the kind that is discussed in theory.…”
Section: The Gfc and Its Aftermathmentioning
confidence: 99%